Speech Acts and Discourse Makers by Teachers and Students in the Classroom - Sudar Sudar (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
This study aims to describe how is the performance of speech acts and discourse makers in the classroom of senior high schools of Purworejo, central Java. The study used qualitative descriptive. The sample of this study is the three English teachers and their students from three senior high schools. Data taken by recording teachers and students in the classrooms. The findings show that transaction of agreement is highly developed by teachers. For example: ok, ya. Questions and Follow up exchange performed by teachers. Further, negotiate outcome, argumentation, and describing adjacency pair created by teachers. Elicitation acts and information acts are performed by teachers and students. Directive acts is mostly developed by teachers. Students performed directive acts when they are in group discussion.